Pengaruh Kepemimpinan Transformasional, Team Work dan Reward Terhadap Kinerja Karyawan PT Ragam Rasa Raya Kota Bengkulu - Nata Satria Uly; Markoni Markoni; Janusi Waliamin (Universitas Nusantara PGRI Kediri, 2023)
The purpose of this study is to find out how much influence transformational leadership, team work and rewards have on employee performance at PT. Variety of Raya flavors in Bengkulu City. The variables of this research are transformational leadership, team work and rewards. This research is a quantitative approach research. The research population is all employees of PT. Ragam Rasa Raya Bengkulu City, 45 samples with the saturated sample method. The analytical tool used in this study uses SPSS 22. The data analysis method used is multiple linear regression. The results of the study show that (1) Transformational leadership has a significant effect on the performance of employees at PT. Ragam Rasa Raya Bengkulu City, (2) Team work has a significant effect on the performance of employees of PT. Ragam Rasa Raya Bengkulu City, (3) Rewards have no significant effect on the performance of employees of PT. Ragam Rasa Raya Bengkulu City, (4) Transformational Leadership, Team work and Rewards influence simultaneously on the performance of employees of PT Ragam Rasa Raya Bengkulu City.